Botanical and Chemical Overview, Traditional Uses and Potential of Anticancer Activity from Several Costus Plants: A Narrative Review - Lina Nafisah; Eli Halimah; Yoppi Iskandar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Plants in the Costus genus are known to have various activities, starting from an antibacterial agent, anti-inflammatory, antioxidant, anticancer, antidiabetic, and so on. From some previous studies that have been conducted, it is stated that some Costus plants have a high potential to be a prospective anticancer candidate in the future. This review will discuss botanical and chemical overview, traditional uses, and potential anticancer activity of several Costus plants, namely C.speciosus, C.igneus, C.spiralis, and C.pictus. In conclusion, anticancer activity assay was carried out by several methods using various cell cultures resulting in an IC50 value ranging from strong and very strong, with the strongest potency belonging to C.speciosus with an IC50 value of 13.87 µg/ml. In addition, the active phytoconstituent, mainly diosgenin, contributes to the anticancer activity, which also strengthens the potential of Costus plants.